PENGARUH CASH TURNOVER DAN RECEIVABLE TURNOVER TERHADAP PROFITABILITAS PADA PERUSAHAAN JASA SUB SEKTOR PROPERTY AND REAL ESTATE PERIODE 2014-2019 - Sugito Sugito, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This study aims to determine and analyze the effect of cash turnover and accounts receivable turnover on profitability in the property and real estate sub sector services companies listed on the Indonesia Stock Exchange for the period 2014-2019. The research method is to use quantitative analysis. From the results of research that has been carried out, simultaneous variable cash turnover and accounts receivable turnover has a significant positive effect on profitability (ROA) in property and housing sub sector services companies listed on the Indonesia Stock Exchange in 2014-2019. Partially cash turnover has a significant negative effect on profitability (ROA). Accounts receivable turnover has a significant positive effect on profitability (ROA)